HBXIP overexpression is correlated with the clinical features and survival outcome of ovarian cancer - Yixuan Wang; Jie Sun; Nan Li; Shuanlong Che; Tiefeng Jin; Shuangping Liu; Zhenhua Lin (BMC, 2017)
Abstract Background Accumulated evidence has demonstrated that Mammalian hepatitis B X-interacting protein (HBXIP) has broad roles in cancer. Although HBXIP is associated with a variety of cancers, the HBXIP protein expression level and its clinical significance in ovarian cancer have not yet been determined. The aim of this study is to investigate the association between HBXIP expression and the clinicopathological features of ovarian cancer patients to determine whether HBXIP may be correlated with a poor prognosis in ovarian cancer patients. Methods HBXIP protein expression was assessed in a well-characterized series of ovarian cancer tissue samples (n = 120) with long-term follow-up, using immunohistochemistry to determine the location pattern and expression of HBXIP in ovarian cancer. The localization of HBXIP was detected in SKOV-3 ovarian cancer cells using immunofluorescence (IF) staining. The relationship between high HBXIP expression and the clinicopathological features of ovarian cancer patients was analyzed by Chi-square and Fisher's exact test. Overall survival (OS) rates of all the ovarian cancer patients were calculated using the Kaplan-Meier method, and univariate and multivariate analyses were performed using the Cox proportional hazards regression model. Results IF staining revealed strongly positive signals for HBXIP in both cytoplasm and nucleus, but mainly in the cytoplasm of SKOV-3 ovarian cancer cells. High HBXIP expression was predominantly observed in ovarian cancer tissues but not the adjacent non-tumor ovarian tissues. The strongly positive rate of HBXIP expression was 60.0% (72/120) in ovarian cancer and was significantly higher than in adjacent non-tumor tissues (17.4%, 4/23) (P = 0.000). High HBXIP expression was positively correlated with the occurrence of lymph node metastases (P = 0.025), histological grade (P = 0.036) and clinical stage (P = 0.003). The patients with high HBXIP expression had lower overall survival (OS) rates. Moreover, multivariate analysis indicated that HBXIP, in addition to the clinical stage, was a significant independent prognostic factor in patients with ovarian cancer. Conclusions High-level expression of HBXIP is associated with the progression of ovarian cancer and may be an effective biomarker for poor prognostic evaluation as well as a potential molecular therapy target for ovarian cancer patients.